Medical Management after Liver Transplantation - Dave, Shravan; Ajmera, Veeral H. (Digestive Disease Interventions, 2019)
Medical management of the liver transplant recipient requires consideration of the complex interactions between the transplanted liver, immunosuppression and all organ systems. An aging transplant population, improvement in long-term liver transplant outcomes, and the increase in nonalcoholic fatty liver disease as an indication for transplant have amplified the number of co-morbidities among post-transplant patients. In addition to balancing immunosuppression with infection risk, medical management of the transplanted patient includes monitoring for, and treating, recurrence of the primary liver disease, metabolic syndrome, cardiovascular disease, and post-transplant neurologic and renal dysfunction. Additionally, general healthcare maintenance such as management of osteoporosis, immunizations, and screening for malignancy are essential in this high-risk population. In this review, we summarize the evidence behind best practices for the current medical management of the post liver transplant patient.
Keywords: post-liver transplant; immunosuppression; graft loss